Eating Habits and Eating Disorder Associated Behavior in Bipolar Disorder. Issue 12 (December 2022) - Hirte, Teresa S.; Fellendorf, Frederike T.; Unterrainer, Human-Friedrich; Dalkner, Nina; Bengesser, Susanne A.; Birner, Armin; Platzer, Martina; Queissner, Robert; Holasek, Sandra; Schwerdtfeger, Andreas; Reininghaus, Eva Z.
Abstract: A relevant comorbidity of bipolar disorder (BD) is eating disorders (EDs). Crossed vulnerability factors as eating disorder–specific symptoms (EDSSs) may trigger the onset of both disorders in either direction. The Structured Inventory for Anorexic and Bulimic Eating Disorders for Self-Report was used to examine the occurrence of EDs in euthymic/subsyndromal individuals with BD ( n = 86) and healthy controls ( n = 86) matched for age and sex. Furthermore, we explored EDSSs with the subscales "general psychopathology and social integration, " "bulimic symptoms, " "body image and slimness ideal, " "sexuality and body weight, " "counteract, " and "atypical binge." Higher rates of all EDSSs were reported in BD. Younger individuals with BD showed higher expression in "bulimic symptoms, " "body image and slimness ideal, " and "atypical binge" subscales. No participants fulfilled ED diagnosis. The findings show a link between EDSS and BD. Clinicians should pay attention to a multimodal intervention, considering risk factors, investigating eating habits and ED associated behaviors.